2020
DOI: 10.1186/s12872-020-01467-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical picture, management and risk stratification in patients with cardiogenic shock: does gender matter?

Abstract: Background: Early recognition and risk stratification are crucial in cardiogenic shock (CS). A lower adherence to recommendations has been described in women with cardiovascular diseases. Little information exists about disparities in clinical picture, management and performance of risk stratification tools according to gender in patients with CS. Methods: Data from the multicenter Red-Shock registry were used. All consecutive patients with CS were included. Both CardShock and IABP-SHOCK II risk scores were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
4
9
0
Order By: Relevance
“…Consistent with our cohort, previous studies have also found women presenting with CS to be significantly older than men [ 12 , 16 , 17 , 18 , 19 , 22 ], however, the mean age of both groups in our study (76 years in women and 70.8 in men) were much higher than those already reported. Collado-Lledó et al reported mean ages of 67 and 64 years old for women and men, respectively [ 22 ]. Similiarly, Kunadian et al described mean ages of 69.9 and 64.2 years old for the female and the male groups, respectively [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with our cohort, previous studies have also found women presenting with CS to be significantly older than men [ 12 , 16 , 17 , 18 , 19 , 22 ], however, the mean age of both groups in our study (76 years in women and 70.8 in men) were much higher than those already reported. Collado-Lledó et al reported mean ages of 67 and 64 years old for women and men, respectively [ 22 ]. Similiarly, Kunadian et al described mean ages of 69.9 and 64.2 years old for the female and the male groups, respectively [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, lactate and creatinine levels, as well as estimated glomerular filtrate rate at admission, were similar in both groups. Notwithstanding this finding, and similar to previous reports in the field [ 12 , 22 ], LVEF in women was found to be significantly higher ( p = 0.037).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations